The Strategy of Islamic Boarding School Supervisors in Sanctioning the Behavior of Truant Santri - Mega Adyna Movitaria; Zahratul Aini Amr; Melda Delvia (Institut Agama Islam Sumatera Barat, 2023)
Boarding school like a home for the students which is a blend of three educations; namely family education, school education, and community education. Islamic boarding schools have an important role in educating the character of students, especially students who have bad habits such as skipping classes or running away from the hostel. A strategy is needed to overcome and address this behavior of truant students. Therefore, this study aims to: (1) find out the strategies used by Islamic boarding school supervisors in addressing the behavior of truant students, (2) describe the strategy of the supervisor in addressing this behavior. This study uses a qualitative-descriptive method. The research subjects were Nurul Yaqin Al-Hidayah and Nurul Yaqin Aswaja Islamic boarding schools who were conducted by interviewing the subject directly. The results of the study show that students who skip classes will be called into the counseling room and asked about the cause and advised if skipping is done just once. If it still continues, then by calling his parents to the hut. In addition, students who skip classes are also given sanctions such as cleaning the toilet